The Use Of Props As To Increase Interest And Understanding Mathematics Concepts Ability Elementary School Students - Yusritawati, Ita; Julaerah, Ai; Nurfirdaus, Nunu; Nurul Arifin, Syifa Afidah (Program Magister Pendidikan Matematika, Pascasarjana, Universitas Pasundan in collaboration with Asosiasi Guru Matematika Indonesia (AGMI) and Indonesian Mathematics Educators' Society (IMES), 2023)
This Researched study is a mixed methods (Mixed Method) type “Embedded Design” with an experimental type of study design shaped models with pretest-posttest control group design, which aims to conduct studies that focus on the use of teaching props that could be expected to improve the understanding of mathematical concepts and their impact on student interest in Elementary School. Instruments used in this research are to test the ability to understand mathematical concepts, students’ interest questionnaire with the Likert scale, observation sheets, and interviews. Based on data analysis we concluded that (1) The ability to understand mathematical concepts of superior and low students who use props better than the ability to understand mathematical concepts of superior and low students who obtain conventional learning, (2) The ability to understand mathematical concepts of the superior and low students using props by cooperative learning type. (3) There is a significant correlation between students' understanding of mathematics and students' interest in learning mathematics.